OVERVIEW OF THE POTENTIAL DEVELOPMENT OF NATURAL TOURISM OBJECTS AND ATTRACTIONS OF PANTAI CEMARA INDAH GOSONG TELAGA IN NORTH SINGKIL SUB-DISTRICT, ACEH SINGKIL REGENCY - Padriadi Wiharjokusumo; Novita Romauli Saragih; Ayu Lestari Malau (Jurnal Ilmiah Akomodasi Agung, 2021)
Cemara Indah GosongTelaga beach is one of the attractions located in the village of GosongTelaga, North Singkil sub-district, Aceh Singkil Regency, the potential of this beach is its natural beauty, a fairly wide stretch of white sand. However, the management of this beach is not well managed. The purpose of this study was to find out how the management efforts at Natural Tourism Objects and Attractions of Pantai Cemara Indah Gosong Telaga In North Singkil Sub-District,Aceh Singkil Regency. The research method carried out by the researchers is descriptive qualitative by direct research to the field (field research) and literature research (library research), namely reading books related to the researchers' writings. The conclusions of the research carried out by researchers: (1) The potential and attractiveness of Cemara Indah GosongTelagabeach in North SingkilSub-district, Aceh Singkil Regency is that it has beautiful natural potential and is still natural. (2) The management of Cemara Indah GosongTelaga beach has problems or obstacles faced in developing Cemara Indah GosongTelaga beach due to the lack of procurement and development of the required facilities, and infrastructure. (3) Efforts in the development of Cemara Indah GosongTelagabeach include increasing physical development, facilities and infrastructure as well as tourist facilities such as hotels or accommodations, restaurants, clean water, prayer rooms, electricity, telecommunications, roads, bridges, parking lots, security posts, health clinics, and others. The researchers’ suggestion from the research results is that the government and other related parties (stakeholders)try to develop both facilities and infrastructure in the tourist area of ​​​​Cemara Indah GosongTelaga beach.